Fis Regulates Type III Secretion System by Influencing the Transcription of exsA in Pseudomonas aeruginosa Strain PA14 - Deng, Xuan; Li, Mei; Pan, Xiaolei; Zheng, Ruiping; Liu, Chang; Chen, Fei; Liu, Xue; Cheng, Zhihui; Jin, Shouguang; Wu, Weihui (Frontiers in Microbiology, 2017)
Fis is a versatile DNA binding protein in bacteria. It has been demonstrated in multiple bacteria that Fis plays crucial roles in regulating bacterial virulence factors and optimizing bacterial adaptation to various environments. However, the role of Fis in Pseudomonas aeruginosa virulence as well as gene regulation remains largely unknown. Here, we found that Fis was required for the virulence of P. aeruginosa in a murine acute pneumonia model. Transcriptome analysis revealed that expression of T3SS genes, including master regulator ExsA, was defective in a fis::Tn mutant. We further demonstrate that the continuous transcription of exsC, exsE, exsB and exsA driven by the exsC promoter was required for the activation of T3SS. Fis was found to specifically bind to the exsB-exsA intergenic region and plays an essential role in the transcription elongation from exsB to exsA. Therefore, we found a novel role of Fis in the regulation of exsA expression.